Identifikasi Hama pada Tegakan Cendana (Santalum Album L.) di Hutan Rakyat Cendana Nunka Wilayah Dusun III, Desa Ponain, Kecamatan Amarasi, Kabupaten Kupang - Nadya Sarwina Molana; Yasinta L. Kleden; Maria M. E. Purnama (Wana Lestari, 2022)
The purpose of this study was to identify the types of pests in sandalwood stands, symptoms of damage, population numbers, and morphological characteristics of pests in sandalwood stands (Santalum album L.) in the Cendana Nunka Community Forest, Hamlet III Region, Ponain Village, Amarasi District, Kupang Regency. One month from February to March 2020. The data collection method in this study used primary data and secondary data. Furthermore, sampling using plots or plots at the observation location in the form of a diagonal with a size of 10 × 10 m consisting of 5 sub plots of sample units in one unit plot there are 5 sample trees (about 10%) with each sample unit of 1.5 m using sticky traps and taken directly on sandalwood stands aged 9-10 years. Then the samples were identified at the Laboratory, Pests, Faperta, Nusa Cendana University and analyzed using the calculation of absolute damage and non-absolute damage. The results of the research identified and obtained the population of pests that attack sandalwood stands in the Cendana Nunka Community Forest, Hamlet III Region, Ponain Village, Amarasi District, Kupang Regency, armored scale (Chionaspis. sp) of 315.24 individuals/plant. Then mealybug (Nipaecoccus viridis) of 44.84 heads/plant with (IKTM) Non-Absolute Damage Intensity of 33.05%.